Inhibitory Effect of Certain Spices and Herbs Powders and their Extracts on Normal and Pathogenic Meat Microflora - Srihari, K.A.; Harilal , P.T.; Pandey, M.C. (Journal of Meat Science, 2014)
The antibacterial activity of clove, green tea, ginger, garlic, fenugreek and coriander seeds against microflora (heterogeneous) isolated from fresh and spoiled mutton as well as, Escherichia coli (food isolate, biochemically identified) and Staphylococcus aureus (MTCC-96) was evaluated. Both powder as well as ethanolic extract of the spices and herbs were used to establish and compare the inhibitory effect by semi-quantitative and cell enumeration (quantitative) methods. Of the spice and herb powders evaluated (by semiquantitative test), clove exhibited higher degree of inhibition against both fresh and spoiled mutton micro-flora. Green tea, ginger and garlic powders were effective against fresh meat micro-flora, while for spoiled meat micro-flora, green tea exhibited limited inhibitory effect and ginger and garlic were not effective. Fenugreek and coriander were found to be least effective for both fresh and spoiled meat micro-flora at the levels used. Ethanolic extracts equivalent to 1 g and 2 g clove powder exhibited complete inhibition in case of fresh mutton flora (SPC 5.81 log cfu/g) and spoiled mutton flora (SPC 8.91 log cfu/g) respectively. Other spices/ herbs viz., green tea, garlic and ginger exhibited comparatively lesser degree of inhibition for the same concentrations as compared to that in case of clove. With respect of pathogens, clove exhibited 100% inhibition where as other spices/herbs showed comparatively lower inhibitory activities. These spices/ herbs were found to be useful in extending the shelf life of raw mutton since significant (p
Keywords: Inhibitory activity; Spices and herbs; Meatmicro-flora; Pathogens; Shelf life extension